Introduction for Forum on Jonathan Ebel's From Dust They Came: Government Camps and the Religion of Reform in New Deal California and Lloyd Barba's Sowing the Sacred : Mexican Pentecostal Farmworkers in California - Greene, Alison Collis (Church history, 2024)
Lloyd Daniel Barba, assistant professor of religion at Amherst College, and Jonathan H. Ebel, professor and head of Religion at the University of Illinois, have written a pair of books that reframe the study of sacred space and the nature of religious communities while advancing the study of religion in the U.S. West. Each book does important theoretical and interpretive work on its own. Together, the books offer a rich picture of California's Central Valley, a subregion that Kori Walker-Price notes has been "dismissed as a site of serious study" because of its factory farms, its mobile labor force, and its distance from the more iconic scenery of California and the west. But they do more than that. Both use their subjects to make larger arguments and claims about religion, methodology, power, race, and gender in the United States.